Bring your own devices (BYOD) survival guide - Keyes, Jessica, 1950- (Taylor & Francis, 2013)
"This book explains and then helps readers live with the psycho-techno phenomenon that is bring your own technology (BYOT). Readers will learn how to understand these new end-users and their demands, as well as the strategic and tactical ramifications of these demands. Next, it covers the broad range of technical considerations such as selection, connectivity, training, support, and security. The text includes best practices and case studies of well-known companies, including IBM, Ford, and CarFax"--